2004
DOI: 10.1021/nl0484907
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Water Confined in Nanometer Channels of Closed Carbon Nanotubes

Abstract: We present a method to fill 2−5-nm-diameter channels of closed multiwalled carbon nanotubes (MWNT) with an aqueous fluid and perform in situ high-resolution observations of fluid dynamic behavior in this confined system. Transmission electron microscope (TEM) observations confirm the successful filling of two types of MWNTs and reveal disordered gas/liquid interfaces contrasting the smooth curved menisci visualized previously in MWNT with diameter above 10 nm. Electron energy loss spectroscopy (EELS) and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
203
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(211 citation statements)
references
References 36 publications
(80 reference statements)
6
203
0
Order By: Relevance
“…Recent investigations have increased our understanding of confined water, showing that, in nanoscopic proportions, many water properties differ drastically from those of bulk water [10,11,12]. In particular, an excellent model is water confined in carbon nanotubes, which have been adopted in many previous studies [13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Among these interesting investigations, Koga et al investigated water inside single-walled carbon nanotubes (SWCNTs) of diameter 1.1∼1.4 nm and found that water forms ice nanotubes composed by a rolled square ice sheet [14,15,16].…”
mentioning
confidence: 99%
“…Recent investigations have increased our understanding of confined water, showing that, in nanoscopic proportions, many water properties differ drastically from those of bulk water [10,11,12]. In particular, an excellent model is water confined in carbon nanotubes, which have been adopted in many previous studies [13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Among these interesting investigations, Koga et al investigated water inside single-walled carbon nanotubes (SWCNTs) of diameter 1.1∼1.4 nm and found that water forms ice nanotubes composed by a rolled square ice sheet [14,15,16].…”
mentioning
confidence: 99%
“…However, studying the structural dynamics of nanodroplets is experimentally challenging because one needs to be able to externally induce the movement and be able to image the subsequent dynamic process of nanoscale droplets. Although atomic force microscope probes have measured the interfacial forces between liquids (18) and scanning transmission electron microscopy (TEM) has imaged small numbers of static water molecules confined in carbon nanotubes (19), these approaches fail to directly relate structure and dynamics of nanoscopic liquids. The ability to externally induce the movement and directly study the motion of model nanodroplets in contact with substrate interface may provide an insight to dynamic properties of interfacial water by experimentally complementing theoretical simulations.…”
mentioning
confidence: 99%
“…Simulations revealed that DNA molecules enter CNT spontaneously with the aid of van der Waals and hydrophobic interaction forces 47 and the translocation events can be driven by an electric field. 45 So far, experimental studies using nuclear magnetic resonance (NMR), 48 x-ray diffraction (XRD), 49 IR spectroscopy, 50 transmission electron microscope (TEM) 51 and scanning electron microscope (SEM) 52 have confirmed that water could enter and form ordered structures in SWCNTs or MWCNTs. More direct transport measurements are finished by using a CNT membrane, which consists of millions of carbon nanotubes in parallel.…”
Section: Carbon Nanotube Based Nanopore/ Nanochannel Devicesmentioning
confidence: 99%
“…98,99 Microscopically the chemical potential of water is lower inside the SWCNT than in the bulk, 43 and water can be transported at many thousand times the speed possible with classical Poiseulle flow. 43,53,54,100 Internal wetting of CNTs has been verified by transmission electron microscopy (TEM) 101 and a number of spectroscopy methods, [102][103][104][105][106][107] showing that water is ordered inside a CNT. The transport of water, ions and small molecules through CNTs has also been studied experimentally using membranes consisting of billions of carbon nanotubes in parallel.…”
Section: Introductionmentioning
confidence: 99%